Self-Assembly Properties and Aggregation Behavior of Amphiphilic Water-Dispersed Polyester with Different Contents of Sulfonate Groups in an Aqueous Solution - Wang, Jie (Langmuir : the ACS journal of surfaces and colloids, 2023)
Amphiphilic polymer water-dispersed polyester (WPET) has an important application value in the textile field. However, due to the potential interactions among water-dispersed polyester (WPET) molecules, the stability of their solution is susceptible to external factors. This paper focused on the self-assembly properties and aggregation behavior of amphiphilic water-dispersed polyester with different contents of sulfonate groups. In addition, the effects of WPET concentration, temperature, and Na+, Mg2+, or Ca2+ on WPET aggregation behavior were systematically investigated. The results show that compared with the low sulfonate group content of WPET, the high sulfonate group content of the WPET dispersion has higher stability with or without a high electrolyte concentration. In contrast, dispersions with low sulfonate group content are very sensitive to electrolytes and aggregate immediately at low ionic strength. WPET concentration, temperature, and electrolyte play important and complex roles in controlling the self-assembly properties and aggregation behavior of the WPET. The increase in WPET concentration can promote the self-assembly of WPET molecules. With the increase in temperature, the self-assembly properties for water-dispersed WPET are significantly reduced, resulting in enhanced stability. In addition, the electrolytes Na+, Mg2+, and Ca2+ in the solution can significantly accelerate the aggregation of WPET. This fundamental research on the self-assembly properties and aggregation behavior of WPETs can be used to effectively control and improve the stability of WPET solutions and provide guidance for the prediction of stability for WPET molecules not yet synthesized